2019
DOI: 10.1111/1346-8138.15031
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus ointment for the treatment of superficial kaposiform hemangioendothelioma and tufted angioma

Abstract: Kaposiform hemangioendothelioma (KHE) and tufted angioma (TA) are rare infiltrative vascular tumors. Currently, no standard treatment regimens exist for KHE/TA. The purpose of our study was to evaluate the efficacy and safety of topical application of tacrolimus for superficial KHE/TA. We examined six patients with superficial KHE/TA. All patients were treated with tacrolimus 0.1% ointment twice daily for at least 12 months. The response rate was 100%, including three nearly complete remissions. Only one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Several case reports and case series have reported success using topical sirolimus and tacrolimus ointment in superficial KHE/TA. The investigators have shown a good response of KHE/TA to twice daily topical application of these drugs [130,131]. Tacrolimus is an anti-T-cell immunosuppressive drug that is FDA-approved as a topical gel formulation (available in a concentration of 0.03 and 0.1%) for the treatment of cutaneous inflammatory/fibrotic diseases [132].…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Several case reports and case series have reported success using topical sirolimus and tacrolimus ointment in superficial KHE/TA. The investigators have shown a good response of KHE/TA to twice daily topical application of these drugs [130,131]. Tacrolimus is an anti-T-cell immunosuppressive drug that is FDA-approved as a topical gel formulation (available in a concentration of 0.03 and 0.1%) for the treatment of cutaneous inflammatory/fibrotic diseases [132].…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Although surgical excision has been recommended for most cases as a specific treatment, medication therapy for TA with large lesion range and pain remains a clinical intricacy 1,5 . In a previous study, we have reported two patients with TA showing response after topical tacrolimus application 6 . Here, we further report a case of TA with severe pain been treated successfully by tacrolimus ointment.…”
Section: Figurementioning
confidence: 70%
“…1,5 In a previous study, we have reported two patients with TA showing response after topical tacrolimus application. 6 Here, we further report a case of TA with severe pain been treated successfully by tacrolimus ointment.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In total, 137 patients were diagnosed with KHE during this 8-year interval. These KHE patients had previously been invited to participate in studies of epidemiologic factor, clinical feature, and/or treatment analyses [ 7 13 ].…”
Section: Methodsmentioning
confidence: 99%